Does debt moderate the impact of family commissioner boards on company performance in Indonesia? - Said Musnadi; Mahdani Ibrahim; Sofyan Idris (Problems and Perspectives in Management, 2023)
This study aims to investigate the influence of family commissioner boards (FCBs) on the operational efficiency of companies in Indonesia that use debt as a control tool, which includes bank and non-bank debt. Using the two-step GMM-First Difference estimation method, the research sample consists of 121 family-owned companies using unbalanced panel data from 2009 to 2018. This investigation produces several significant findings. Firstly, the results of the analysis show that the presence of family representatives on the board of commissioners has a negative impact on overall company performance. These observations suggest that FCBs may prioritize the interests of family shareholders over minority shareholders, which indicates entrenchment behavior. Second, the analytical results reveal that debt plays a moderating role in the influence of FCB on company performance. Debt acts as a deterrent to entrenchment behavior, thereby improving firm performance. Third, the results of the analysis did not find significant differences in FCB entrenchment behavior between companies that have bank debt and companies that have non-bank debt. These findings have significant policy implications for regulatory bodies in Indonesia regarding the governance of family-owned companies. It is vital to establish a mechanism for appointing family members to the board of commissioners that protects the interests of all shareholders and promotes a fairer corporate landscape.